Public Participation in Policy Formulation in the Era of Digitalization of Government - Judijanto, Loso; Nurmalasyiah, Nurmalasyiah; Silam, M. Mochtar Mandala; Riduan, Akhmad (PT. Anagata Sembagi Education, 2025)
Digital transformation in government has opened up new opportunities to strengthen public participation in the policy formulation process. Through various digital platforms such as e-government and social media, interactions between the state and citizens have become more open, fast, and participatory. However, digitalization is not without challenges. Infrastructure gaps, digital literacy, and the tendency towards participatory symbolism (tokenism) have the potential to create new exclusions in the practice of digital democracy. This study uses a descriptive qualitative approach with a literature study method to evaluate the extent to which digital governance is able to encourage substantive public participation. The results of the study show that the success of digital democracy is not enough just by providing technology, but requires institutional reform and ethical-political commitment to create a fair and inclusive deliberative space. Within the framework of deliberative democracy, citizen participation must be positioned as an integral element that influences the substance of policy, not just a procedural formality. These findings emphasize the need for policy strategies that are not only technocratic, but also sensitive to socio-political dimensions, including the redistribution of power, increasing digital-political literacy, and ensuring the involvement of marginalized communities. Thus, digitalization in government will only be meaningful if it is able to bridge the participation gap and encourage democratic practices that are more inclusive, deliberative, and have a real impact on the public.